PENERAPAN SANKSI PERUBAHAN PERILAKU DALAM PERKARA PERSAINGAN USAHA - Graceya Iranita Tarigan (2022)
Changes in behavior are one of the new sanctions whose implementation procedures are regulated in PerKPPU 1/2019 which regulates how to handle cases that commit monopolistic and anti-competitive actions. The behavior change is stated in a Behavior Change Integrity Pact (PIPP) which contains adjustment points that need to be made by the Reported Party. In its implementation, there have been two cases that were sanctioned for behavior change, namely the KPPU's decision regarding anti-competition actions in the form of discrimination carried out by Garuda Indonesia in the selection of Umrah partners and discriminatory practices carried out by the Lion Group related to cooperation in the sale of cargo capacity. However, in its implementation, there are violations committed by Business Actors against the commitments that have been stated in the PIPP. The purpose of this paper is to analyze the application of behavior change sanctions in business competition cases and see the parameters of violations against PIPP. This research method uses a normative juridical approach which is carried out by approaching laws and cases and using primary legal materials in the form of AntiMonopoly Laws and regulations relating to business competition. The results of the study show that in the application of behavior change sanctions, consideration is carried out by considering the form of the violation, and the losses resulting from the violation. Then, the commitment of the Business Actor in carrying out Behavior Change is stated in the PIPP whose supervision is carried out by the Commission Council for 60 (sixty) days. If there is a violation of the PIPP, the examination will continue to the next trial.